REALISASI FONEM VOKAL BAHASA INDONESIA - Mohammad Fakhrudin; Bagiya Bagiya (p-ISSN 2356-0576, 2017)
Abstract: This research aims at describing the realization of all vowel phonemes in Indonesia language. It is expected that this research will be advantageous to all of the Indonesia language speakers, particularly to the teachers and students. Moreover, the findings of this research are also expected to be inspiring to the linguists in Indonesia to do research more comprehensively. The research approach used in this research is qualitative-descriptive. The data were collected using recording, listening, and noting technique. The data that are suitable with this research are noted in data-noting form. The instrument used in this research is the researcher himself, equipped with recorder and data-noting form. The data-noting form is the saved in the hard disc. Then, the data are analysed using distributional method with minimal pair technique and replacement technique. The results of analysis are presented using informal technique. According to this research, it can be concluded that (1) the realization of vowel in Indonesia language consists of two types, i.e. (a) following the rules, and (b) violating the rules; and (2) the violation of vowel realization is found in vowels /i/, /u/, and /o/ in closed position and also in derivative words. The violation is also found in acronym. The violation of vowel realization /u/ is found in the acronym of Indonesia original words. Meanwhile, the violation of vowel realization /e/ and /ә/ not only causes meaning differences, but also does not cause meaning differences. Vowel / ә /, realized with [ε], can cause meaning differences. There are also vowels in open syllable that are followed by different vowels can produce gliding sound and also can produce [?]. In conversation, poem or song lyrics, and also in certain words, vowel /ә/ can disappear.Keyword: realization of vowel phonemes, the languageAbstrak: Penelitian ini bertujuan mendeskripsikan realisasi fonem vokal bahasa Indonesia.Melalui penelitian ini, diharapkan diperoleh temuan yang berguna bagi penutur bahasa Indonesia, terutama pendidik dan peserta didik. Di samping itu, temuan ini pun diharapkan menginspirasi para pakar linguistik untuk meneliti lebih komprehensif. Dalam penelitian ini digunakan pendekatan deskriptif kualitatif. Data dikumpulkan dengan teknik rekam, simak, dan catat. Data yang sesuai dengan masalah penelitian ini dicatat dalam form pencatat data. Instrumen yang digunakan dalam pengumpulan data ini adalah peneliti sendiri dilengkapi dengan perekam dan form pencatat data. Form pencatat data itu disimpan dalam hard disc. Selanjutnya, data tersebut dianalisis dengan metode distribusional dengan teknik pasangan minimal. Hasil analisis disajikan dengan teknik informal. Dalam penelitian ini disimpulkan bahwa (1) realisasi vokal bahasa Indonesia terdiri atas dua macam, yakni (a) sesuai dengan kaidah dan (b) menyimpang kaidah; dan (2) penyimpangan realisasi vokal terdapat pada vokal  /i/, /u/, dan /o/ pada posisi tutup dan pada kata turunan. Penyimpangan pun terjadi pada akronim. Penyimpangan realisasi vokal /u/ terjadi pula pada singkatan kata asli Indonesia. Penyimpangan realisasi vokal /e/ dan /ә/ ada yang menimbulkan perbedaan makna, tetapi ada pula yang tidak menimbulkan perbedaan makna. Vokal /ә/ jika direalisasikan dengan [ε] dapat menimbulkan perbedaan makna. Ada vokal pada suku buka yang diikuti vokal yang berbeda dapat menimbulkan bunyi peluncur dan ada pula yang menimbulkan [?]. Dalam percakapan, teks puisi, atau lagu, pada kata-kata tertentu, vokal /ә/ dapat hilang.Kata kunci: realisasi fonem vokal, bahasa Indonesia